A cDNA Cloning of a Novel Alpha-Class Tyrosinase of Pinctada fucata: Its Expression Analysis and Characterization of the Expressed Protein. (10th April 2014) - Takgi, Ryousuke; Miyashita, Tomoyuki
Abstract : Tyrosinase plays an important role in the formation of the shell matrix and melanin synthesis in mollusks shells. A cDNA clone encoding a 47 kDa protein was isolated from the pearl oyster Pinctada fucata . The cDNA was 1, 957 base pairs long and encodes a 417 residue protein that has extensive sequence identity with tyrosinase (polyphenol oxidase: EC 1.14.18.1). This tyrosinase-like protein, termed PfTy, contains an N-terminal signal sequence and the two copper-binding domain signatures (CuA and CuB), suggesting that PfTy belongs to the α -subclass of type-3 copper proteins. Enzyme activity of PfTy was examined by a spectrophotometric method using the translation product derived from an S30 T7 high-yield protein expression system. Tyrosinase activity was seen in this recombinant product. RT-PCR analysis showed that PfTy mRNA was expressed in the mantle pallial, but not in the mantle edge. Therefore, PfTy may participate in insoluble shell matrix formation of the nacreous layer. PfTy expression was also observed in the foot, liver, and adductor muscle, suggesting that PfTy participates in the synthesis of melanins, which are effective scavengers of free radicals formed in multiple intracellular oxidative processes. This is the first report of a novel α -class tyrosinase from the pearl oyster P. fucata .